Tinjauan Bibliometrik Produktivitas Penelitian Desain Interaktif (Interactive Design) Di Indonesia - Adiwijaya, D Rio (Jurnal Bahasa Rupa, 2023)
This research was conducted to review the productivity of research on the topic of interaction design, especially in Indonesia, based on the Scopus database. The method used in this research is bibliometric analysis. Based on the results of the search conducted, 829 documents were found related to the topic of interaction design in Indonesia. The number of documents continued to grow every year during this period. This can be seen from the number of documents, which in 1996 only increased to 1 document, increasing to 118 documents in 2022. The publication source with the highest number of documents is the Journal of Physics Conference Series with a total of 191 documents. While the dominant document type is in the form of conference papers with a total of 487 documents. The affiliate with the highest number of documents is the Indonesian University of Education with a total of 65 documents. While related science research fields that predominantly discuss interaction design topics are computer science with a percentage of 17.7% or 260 documents .